OPENNESS OF THE ECONOMY AS A CONDITION FOR INTERNATIONAL COOPERATION DEVELOPMENT - R. V. Kashbrasiev (Финансы: теория и практика, 2017)
To reveal the role of openness of a national economy in the system of conditions and factors of international industrial cooperation development.The system approach based on such scientific methods of theoretical and empirical studies as observation and comparison, analysis and synthesis, induction and deduction, as well as mathematical and statistical methods for economic analysis.The main types of openness of the economy were identified; contradictory impact of economic openness on international cooperation was defined; at the same time, it was shown, based on projections of reproductionalopenness of the economy of the Republic of Tatarstan as a region of the Russian Federation and the interpretation of their results, that the subjects of the Russian economy were deeply embedded into the global reproduction networks.Scientific novelty: In the article, through the use of complex of methods, the role of openness of the economy in the context of innovative development and economic security of the country was investigated; embeddedness of international production networks in the Russian economic system was proved; first time the term “cooperational openness of the economy” was presented and analyzed.Practical value: Key points and conclusions of the article may be used in the development of the main directions of foreign economic activity of the country and its regions.